Lender individualism and monitoring: Evidence from syndicated loans - Bermpei, Theodora; Degl’Innocenti, Marta; Kalyvas, Antonios Nikolaos; Zhou, Si (Journal of Financial Stability, 2023)
This paper addresses the question, “Does lenders’ culture affect their monitoring efforts and style?”, by exploring whether lender individualism affects the loan monitoring of U.S. borrowers for a sample of 27,164 syndicated loan facilities granted between 1998 and 2017. We proxy lender individualism based on the ancestral country of origin of the lead bank's CEO. We show that lender individualism leads to a less stringent monitoring style. We find that individualist lenders resort less to covenant monitoring, impose less strict contract terms, such as performance pricing and rely more on soft information. We also provide evidence that individualist lenders retain a larger loan share and deal with a larger number of lenders. Finally, we find that some governance characteristics (board size and percentage of female directors) and other CEO features (cash compensation, tenure, and non-duality) moderate the negative association between lender individualism and loan monitoring.